Sosialisasi Upaya Pencegahan Banjir Menggunakan Sumur Resapan di Kalurahan Timbulharjo Kabupaten Bantul - ASIH, ANDREA SUMARAH; Bernadeta Subandini Astuti (ReTII, 2024)
Timbulharjo sub-district, as part of Kapanewon Sewon, is categorized as a developed sub-district, and has experienced very rapid development progress. The impact of this development includes the reduction in agricultural land. This is because agricultural land has experienced conversion, both for housing and public facilities such as schools, offices, factories, hotels and tourist attractions. Considering that Timbulharjo Subdistrict is crossed by two large rivers, namely the Winongo River and the Code River, land conversion without being accompanied by replacement of catchment land or a good drainage system will cause a big problem, namely the potential for rain runoff which can cause inundation (flooding). This incident of inundation (flooding) has been proven to have occurred in several areas in Timbulharjo District, one of which was at Timbulharjo Elementary School on March 22 2021. Therefore, efforts need to be made to reduce the potential for flooding, one of which is with a simple drainage system that can be implemented by rural communities. . This activity aims to provide insight and knowledge to the public regarding one way to overcome the danger of flooding with absorption wells. The form of activity chosen was in the form of counseling and outreach to community members, one of which was the PKK women’s group. The results achieved from this outreach activity are the formation of a community that understands flood management efforts using infiltration wells.